Genetic diversity analysis of the rice blast pathogen population of two locations in Cuba - Fuentes, J.L; Correa Victoria, Fernando J.; Escobar, F.; Mora, L; Duque E., Myriam Cristina; Deus, J.E.; Cornide, MT (2003)
The genetic structure of rice blast pathogen populations was studied using 149 and 107 monoconidial isolates from Los Palacios and Sur del Jíbaro rice production locations in the western and central regions of Cuba, respectively. These isolates were collected from 35 rice genotypes and total DNA from each isolate was digested with the EcoRl enzyme and probed with a dispersed Magnaporthe grisea repeated sequence (MGR586), which has been widely used in the population analysis of this fungus. MGR586 DNA fingerprinting groups were identified based on DNA restriction fragment length polymorphism similarities. This analysis allowed the identification of 134 haplotypes that were partitioned into four highly related genetic groups. The mean similarity between groups ranged from 75 to 85%. Group A was predominant in both locations and was composed of 84.7% of all monoconidiol isolations from 33 rice genotypes. Isolates from groups B, C and D were associated with one or a small number of very related varieties in the LP region. Genetic diversity estimates between and within the pathogen collection showed a wider diversity in pathogen populations at the western rice region. This analysis also suggested that the migration of this pathogen could have occurred from the western to central rice regions in Cubo. These results suggested that the specific features of the Cuban fungal populations would be particularly useful for selecting germplasm sources for more durable blast-resistance breeding.